“My dear Phaedrus, where is it you are going, and where have you come from?”: An Interpretation of the Opening Line of the Phaedrus - Garcia Dotto, Pedro Mauricio (Revista Archai, 2023)
I argue that the opening line of the Phaedrus proleptically encapsulates the major themes of the dialogue and that paying attention to the opening line enables us to strengthen the identification of psychagogy as the key unifying thread of the whole dialogue. In particular, I argue that the opening line foreshadows the quarrel between Lysias and Socrates over the practical guidance of Phaedrus’ soul; the prominence of friendship in the philosophical form of life; the pertinence of Socrates’ one-on-one, custom-built speeches, vis-à-vis the later conceptualization of rhetoric; the definition of the soul as a source of never-ending movement; as well as the origin (arché) and destiny (télos) of human souls, following the lines of the Palinode.